1997
DOI: 10.1111/j.1445-2197.1997.tb04613.x
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐on‐metal Articulation in Total Hip Arthroplasty: Preliminary Results in 57 Cases

Abstract: Background: Aseptic loosening of hip prostheses may lead to implant failure and necessitate revision surgery. Metal-on-metal hip articulation has characteristics that may minimize prosthesis loosening when compared with other forms of hip articulation. The purpose of the present prospective study was to identify early problems that may contraindicate the use of the 'prosthesis femorale modulaire' (PFM) metal-on-metal prosthesis. Methods: The preliminary results of 57 metal-on-metal total hip arthroplasties per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Recently, several authors [5][6][7][8][9] reported periprosthetic osteolysis and aseptic failure following contemporary total hip arthroplasties with second-generation metal-on-metal articulations, and metal hypersensitivity has been proposed as a mechanism of aseptic loosening of these components 7,[9][10][11] . Most published series have included patients who were followed for a short time [12][13][14][15][16][17] . In this study, we report the results at a minimum of five years following use of a cementless SL-Plus stem (Plus Orthopedics, Rotkreuz, Switzerland) and Bicon-Plus cup (Plus Orthopedics) with a Sikomet SM21 metal-on-metal articulation.…”
mentioning
confidence: 99%
“…Recently, several authors [5][6][7][8][9] reported periprosthetic osteolysis and aseptic failure following contemporary total hip arthroplasties with second-generation metal-on-metal articulations, and metal hypersensitivity has been proposed as a mechanism of aseptic loosening of these components 7,[9][10][11] . Most published series have included patients who were followed for a short time [12][13][14][15][16][17] . In this study, we report the results at a minimum of five years following use of a cementless SL-Plus stem (Plus Orthopedics, Rotkreuz, Switzerland) and Bicon-Plus cup (Plus Orthopedics) with a Sikomet SM21 metal-on-metal articulation.…”
mentioning
confidence: 99%